Transformasi Identitas Diri dalam Konsep Eksistensialisme Kierkegaard dan Relevansinya terhadap Mental Remaja di Indonesia - Annisa Nur Fauziah (UIN Sunan Gunung Djati Bandung, 2023)
This research aims to discuss the transformation of self-identity within the concept of Kierkegaard’s existentialism and its relevance to the mental condition of adolescents in Indonesia. The study utilizes a qualitative approach by applying library research. The formal object of this research is the theory of self-transformation from Kierkegaard’s existentialist thinking, while the material object is the relevance to mental conditions. The scope of the research focuses on adolescent in Indonesia. The results of the discussion in this research indicate that the mental condition of Indonesian adolescents can be analyzed through the transformation of self-identity within Kierkegaard’s existentialism, which consist of three stages. The research concludes that the transformation of self-identity indeed influences the mental condition of adolescents in Indonesia. The study recommends that institutions or social organizations, particularly those involved in the protection and empowerment of adolescents, provide guidance and mentorship to Indonesia adolescents, aiming to cultivate their mental well-being and stability.